Phytochemical Studies on the Stem Bark of Couroupita guianensis Aubl. - Sarkar, P.; Zohora, F.T.; Jabbar, A.; Tareq, F.S.; Hasan, C.M.; Ahsan, M. (Asian Journal of Chemistry, 2013)
From the phytochemical investigation of the stem bark of Couroupita guianensis Aubl (Lecythidaceae) a total of ten compounds have been isolated. An unusual polyketide, an alkaloid, two triterpene caffeates, one diunsaturated ketosteroid, three triterpenes, one phenolic compound and a steroid have been isolated from the stem bark of Couroupita guianensis Aubl. The structures of these compounds were elucidated as cis-4-hydroxymellein (1), tryptanthrin (2), betulin-3b-caffeate (3), lupeol caffeate (4), stigmasta-4,22-dien-3-one (5), betulin (6), b-amyrin (7), lupeol (8), methyl gallate (9), stigmasterol (10) by 1H NMR spectra and confirmed by comparison with previously reported values. The polyketide, cis-4-hydroxymellein is the first report from this family as well as lupeol caffeate and stigmasta-4,22-dien-3-one are also the first\ reports from this plant.